LEARNER CORPUS PROFILES: LEXICAL PECULIARITIES OF GEORGIAN EFL STUDENTS - Makhatadze, Marine (Online Journal of Humanities ETAGTSU, 2022)
This paper focuses on the usability of learner corpus in foreign language research. Teachers, lexicographers and researchers use learner corpus data to measure the most fundamental aspect of second/foreign language knowledge – lexical profiles of the learners. Learner corpora provide a mirror for the learners’ language competence. The paper aims to analyze an ongoing project on the learner corpus of Georgian EFL (English as a foreign language) university students. The language productions that make up our yet ‘baby’ learner corpus include written texts. The reason for bringing learner productions into a corpus rather than examining them individually is the desire to arrive at generalizable findings about language acquisition, i.e. which words can the learners produce and with what degree of appropriateness. Our research seeks to answer the following questions: a) what kind of lexical behaviour is represented in the learner corpus data, and b) what is the potential of giving learners/teachers access to the learners' data? The study and the quantitative information described in the work reflect the characteristics of learner English in terms of part-of-speech distribution and collocation usage. The usefulness and advantages of the corpus-based approach will be demonstrated by employing learner corpus-based activities that can be implemented in an educational environment. Full Text (PDF)